Pelatihan Pembuatan Kerajinan Tangan untuk Meningkatkan Ekonomi Kreatif di Kecamatan Sidoarjo - Rudi Santoso; Siti Aisyah (Journal of Community Action, 2025)
Handicraft making training is one of the efforts to improve the creative economy in society. This research aims to examine the influence of handicraft making training on empowering the creative economy of the community in Sidoarjo District. This training program involves local communities in making handicrafts such as woven bamboo, ceramics and waste-based products that have sales value. This training is designed to provide new skills for participants and open up business opportunities in the creative economy sector. The method used in this research is a quantitative approach with descriptive analysis. Data was collected through interviews and direct observation of training participants, as well as analysis of the economic impact generated after the training. The research results show that this training was successful in improving participants' skills in making handicraft products, broadening their insight into the market, and increasing family economic income. Overall, this training has great potential in strengthening the creative economy sector in Sidoarjo District and can be used as a model for community economic empowerment in other areas.